So $y=\sin^{-1}(x)^2$

I am asked to find $\frac{dy}{dx}$

Using the chain rule I find

$\frac{dy}{dx}$= $2\sin^{-1}(x) * \frac{d}{dx}(\sin^{-1}(x))$

I let

$z = \sin^{-1}(x)$

Multiplying both sides by sin



I want to find the derivative of z so I differentiate both sides

$\frac{d}{dx}(\sin(z))=\frac{dx}{dx}$ = 1

Using chain rule I find $\frac{d}{dx}(\sin(z))=$


So I move $\cos(z)$ over

$\frac{dz}{dx} = \frac{1}{\cos(z)}$

I know that $1 = \cos^2(z)+\sin^2(z)$ so



And this is where I am lost. The working says that from there, $\cos(z)$ is somehow


I am not sure how they came to that. Can someone please explain how they made that leap?

  • $\begingroup$ There's no such thing as "multiplying by sin". You can take the sine of both sides of an equation. $\endgroup$ – G Tony Jacobs Mar 15 '14 at 5:19
  • $\begingroup$ From $\cos z\frac{dz}{dx}=1$, we get $\frac{dz}{dx}\frac{1}{\cos z}=\pm \frac{1}{\sqrt{1-\sin^2 z}}$. Since $\sin z=x$ we get $\frac{dz}{dx}=\pm \frac{1}{\sqrt{1-x^2}}$. But $\sin^{-1} x$ is an increasing function on the interval $[-1,1]$. So we choose the $+$, not the $-$. $\endgroup$ – André Nicolas Mar 15 '14 at 5:23

$$\dfrac{dy}{dx}\sin^{-1}(x)^2=\frac{dy}{dx}\left(\sin^{-1}(x)\right)^2$$ It can be seen that this is a composition of two functions $f(g(x))$, where $f(x)=x^2$ and $g(x)=\sin^{-1}(x)$. Therefore we need to apply chain rule to this. The chain rule is: $$(f\circ g)'(x)= f'(g(x))\cdot g(x)$$ Let,s apply that to our derivative. $$\dfrac{dy}{dx}\left(\sin^{-1}(x))\right)^2$$ $$=2\left(\sin^{-1}(x)\right)^1\cdot \dfrac{dy}{dx}\sin^{-1}(x)$$ There is a well-known derivative for $\sin^{-1}(x)$. It is $\dfrac{1}{\sqrt{1-x^2}}$. $$=2\sin^{-1}(x)\cdot \dfrac{1}{\sqrt{1-x^2}}$$ $$=\dfrac{2\sin^{-1}(x)}{\sqrt{1-x^2}}$$ $$\displaystyle \boxed{\therefore \dfrac{dy}{dx}\sin^{-1}(x)^2=\dfrac{2\sin^{-1}(x)}{\sqrt{1-x^2}}}$$

DERIVATION OF $\dfrac{dy}{dx}\sin^{-1}(x)$:

Want to know how to derive $\dfrac{dy}{dx}\sin^{-1}(x)$? I will show you. It can be found using implicit differentiation. $$y=\sin^{-1}(x), \ \text{so} \ x=\sin(y)$$ We also know that: $$-\dfrac{\pi}{2}\le y \le \dfrac{\pi}{2}$$ Proof: $$\dfrac{d}{dx}x=\dfrac{d}{dx}\sin(y)$$ $$1=\dfrac{d}{dy}\sin(y)\dfrac{dy}{dx}$$ $$1=\cos(y)\dfrac{dy}{dx}$$ $$\dfrac{dy}{dx}=\dfrac{1}{\cos(y)}$$ Remember the Pythagorean identity: $$\sin^2(y)+\cos^2(y)=1$$ $$\cos^2(y)=1-\sin^2(y)$$ $$\cos(y)=\pm\sqrt{1-\sin^2(y)}$$ Because $\cos(y)$ has to be positive (remember, $-\frac{\pi}{2}\leq y \leq \frac{\pi}{2}$), $\cos(y)=\sqrt{1-\sin^2(y)}$. $$\dfrac{dy}{dx}=\dfrac{1}{\cos(y)}=\dfrac{1}{\sqrt{1-\sin^2(y)}}$$ Remember that $\sin(y)=x$. So $\sin^2(y)=x^2$. $$\dfrac{dy}{dx}=\dfrac{1}{\sqrt{1-x^2}}$$ $$\displaystyle \boxed{\therefore \dfrac{dy}{dx}\sin^{-1}(x)=\dfrac{1}{\sqrt{1-x^2}}}$$

  • $\begingroup$ Why not just drop the derivatives $dy/dx$ in the first equation? What does it in fact assert? $\endgroup$ – Ruslan Mar 15 '14 at 9:15

I think they mean $$\frac{dz}{dx} = \frac{1}{\sqrt{1-x^2}},$$ since $$\frac{dz}{dx} = \frac{1}{\cos(z)}$$ and $$x = \sin(z) \implies \cos(z) = \sqrt{1-\sin^2(z)} = \sqrt{1 - x^2}.$$ There is also a rule that $$\frac{d}{dx}\left[\sin^{-1}(x)\right] = \frac{1}{\sqrt{1-x^2}}.$$

  • $\begingroup$ Yes however they simply went from $\frac{+}{-}\sqrt{1-sin^2(z)}$ to $\sqrt{1-x^2}$. We were dealing with a function of z, now we are dealing with x? $\endgroup$ – user88720 Mar 15 '14 at 5:23
  • $\begingroup$ Since $x = \sin(z)$. See the ninth line of your post. $\endgroup$ – Randy Randerson Mar 15 '14 at 5:25
  • $\begingroup$ Awesome, must have missed that. Therefore would it be right to say $\frac{dz}{dx}=\frac{1}{\frac{+}{-}\sqrt{1-x^2}}$ or do remove the negative sign because it is a denominator? $\endgroup$ – user88720 Mar 15 '14 at 5:26
  • $\begingroup$ For why remove the minus sign, please see my comment under your main post. $\endgroup$ – André Nicolas Mar 15 '14 at 5:38

If $y=\sin^{-1} (x)^2$, as you have pointed out:

$$\dfrac{dy}{dx} = 2\sin^{-1}(x) \cdot \frac{d}{dx}(\sin^{-1}(x))$$

We want to find now $\frac{d}{dx}(\sin^{-1}(x))$.

Let $f:[-\frac{\pi}{2}, \frac{\pi}{2}] \longrightarrow [0, 1]$ be $f(x) = \sin(x)$. Since $f\circ f^{-1} = id$


$$(f \circ f^{-1})' = (id)'$$

By the chain rule:

$$f' \circ f^{-1} \cdot (f^{-1})' = 1$$

$$(f^{-1})' = \dfrac{1}{f' \circ f^{-1}}$$


$$\dfrac{d}{dx} \sin ^{-1} (x) = \dfrac{1}{\cos (\sin^{-1} (x))}$$

Which, using trigonometric identities, is equal to $\dfrac{1}{\sqrt{1-x^2}}$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.